Epitope mapping of neutralizing monoclonal antibodies against duck hepatitis B virus. - Cheung, R C (1989)
In this article we report the first topological mapping of neutralizing epitopes of a hepadnavirus. Duck hepatitis B virus is the only hepadnavirus that can replicate and spread from cell to cell in tissue culture. As a result, it is possible to study hepadnaviral neutralization in vitro with this system. To accomplish this goal, we produced a library of monoclonal antibodies against duck hepatitis B virus and identified 12 neutralizing monoclonal antibodies by using an in vitro neutralization assay. The characteristics of six of the neutralizing monoclonal antibodies were further studied by epitope mapping. From the results of competitive binding studies, three distinct neutralizing epitopes were identified on the pre-S polypeptides and one was identified on the S polypeptide. Our findings suggest that antibodies to both the pre-S and S gene products of duck hepatitis B virus can neutralize viral infection in vitro. The pre-S gene product is at least as important as the S gene product in eliciting neutralizing antibodies.